2020
DOI: 10.1111/1365-2656.13375
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stressors interact to impair the performance of bumblebee Bombus terrestris colonies

Abstract: Bumblebees are constantly exposed to a wide range of biotic and abiotic stresses which they must defend themselves against to survive. Pathogens and pesticides represent important stressors that influence bumblebee health, both when acting alone or in combination. To better understand bumblebee health, we need to investigate how these factors interact, yet experimental studies to date generally focus on only one or two stressors. The aim of this study is to evaluate how combined effects of four important stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 156 publications
(191 reference statements)
0
25
1
Order By: Relevance
“…Despite the growing body of evidence documenting negative impacts of pesticides on bumble bees [ 26 , 76 , 77 , 78 , 79 ], and contrary to one of our hypotheses, we found a negative effect of intensity of pesticide use on the site occupancy by bumble bee queens for only one of the eight (groups of) species we detected in orchards, namely, B. ternarius ( Figure 4 C). Aside from the fact that B. ternarius was the third most captured species in our study ( Figure 3 ) and that this may have led to an improved capacity of detecting such an effect, it remains that this result may also stem from interspecific differences in exposure or sensitivity to pesticides.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite the growing body of evidence documenting negative impacts of pesticides on bumble bees [ 26 , 76 , 77 , 78 , 79 ], and contrary to one of our hypotheses, we found a negative effect of intensity of pesticide use on the site occupancy by bumble bee queens for only one of the eight (groups of) species we detected in orchards, namely, B. ternarius ( Figure 4 C). Aside from the fact that B. ternarius was the third most captured species in our study ( Figure 3 ) and that this may have led to an improved capacity of detecting such an effect, it remains that this result may also stem from interspecific differences in exposure or sensitivity to pesticides.…”
Section: Discussioncontrasting
confidence: 99%
“…As expected, species richness was negatively influenced by the intensity of pesticide use. As mentioned above and shown here, evidence of negative effects of pesticides on bumble bee species, such as B. impatiens and B. terrestris, is mounting [ 26 , 76 , 77 , 78 , 79 ]. However, studies looking at the effects of pesticides on bee communities remain scarce, and those that did so while controlling for imperfect species detection are even scarcer.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Ingestion of N. ceranae spores exerts a stress that can reduce cognition. N. ceranae is known to alter the immune system of bees by increasing oxidative responses (Kurze et al, 2016) or modulating the expression of antimicrobial peptides (Antúnez et al, 2009; Botías et al, 2020; Sinpoo, 2018). Stimulation of the immune system of bees with non-pathogenic elicitors, as lipopolysaccharides (LPS), was shown to reduce learning abilities in honey bees, that were less able to associate an odour with a reward (Mallon et al, 2003), and bumblebees, that showed lower performances in odour (Mobley and Gegear, 2018) and colour differential learning tasks (Alghamdi et al, 2008; Mobley and Gegear, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is The copyright holder for this preprint this version posted July 10, 2021. ; https://doi.org/10.1101/2021.07.09.451741 doi: bioRxiv preprint the spatial arrangement of plant species producing nectar or pollen in high quantities (59,79,80) on structuring bumble bee populations. Finally, habitat alterations such as intensified farming practices might also structure populations, in particular through a synergy with natural stressors (81,82).…”
Section: Discussionmentioning
confidence: 99%